Implmentasi Triple Bottom Line Theory Pada PT.Xui Long - Rahayu Wilujeng; Bismo Prayoga; Mohamad Djasuli (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
The Triple Bottom Line (TBL) concept emphasizes that companies are not only concerned with profits in their business activities, but also contribute to society (people) and actively participate in protecting the environment (planet). One application of the TBL concept is Corporate Social Responsibility (CSR). P.T. XUI LONG is a company that implements the Triple Bottom Line (TBL) concept. However, according to the community, this program has drawbacks. Although the company stated that there were no problems in implementing the program. The purpose of this research is to find out how the TBL concept is applied to PT. XUILONG and program evaluation. Documentary studies, in-depth interviews and observation are used as investigative techniques. The data analysis technique used is a qualitative descriptive analysis technique. The result of this study is that PT XUI LONG applies the TBL concept but does not maximize it conceptually. The community is not involved in program planning and evaluation and program evaluation does not run optimally because the receiving community is not involved and the achievement of program objectives is not evaluated.